Patient safety in the distribution of hospital diets – an intervention strategy (Research, Society and Development, 2023)
Among the care offered in the hospital environment, nutritional care is part of the treatment, involving a complex flow of information from admission to the implementation of the dietary prescription. However, the absence of widely adopted operational principles, in addition to process and technology limitations, lead to inaccurate patient identification, predisposing to errors and adverse events. The objective of this study was to analyze the influence of the implementation of a computerized system for the prescription and generation of identification labels for diets in a university hospital in the prevention of adverse events. In order to compare its effectiveness, the time for manually making the identification labels was verified and the trays of the main meals produced were analyzed for the presence of flaws in the assembly to constitute the Near Error Index (IQE), since intervention was carried out in order to avoid adverse events. After the implementation of the computerized system, a reduction in the time to produce labels from 47 ± 22 minutes to 17 ± 8.9 minutes was observed, as well as in the IQE found, whose reduction was from 39.3% to 2.41%. The study showed that the computerization of label production proved to be effective in preventing dietary errors. In addition, it suggests supervision of the entire process of setting up diets to avoid failures and adverse events.